Entrepreneurial Finance Perspective: Highlighting from the Supply Side - Maria Rio Rita; Harjum Muharam (Jurnal Keuangan dan Perbankan, 2018)
The emergence of the entrepreneurial finance theory in developing the financial theory was still relatively new. Up until the early 1990s, the topic of entrepreneurial finance was still rarely discussed, although actually many aspects could be explored more in-depth by academicians. There was no consensus about the definition of entrepreneurial finance. It can be mapped out that past literature studies or previous research just looked at entrepreneurial finance from the financing provider side (supply side). A supply-side test examined the fund provider (financier) perspective as a test center like formal and informal equity (venture, capitalists, angel investors, corporate venturing, crowdfunding), as well as formal and informal debt like bank debt, loans from friends and family members, and the release of other money (mezzanine) to develop start-up companies or micro, small, and medium enterprises. A synthetic meta-analysis in this research integrated and synthesized several qualitative research findings through better descriptions and facilitates the reconceptualization from a study. Based on this study, we found that actually there was still a lot of room from the topic of entrepreneurial finance to become future research, such as from the entrepreneur’s side (demand side) related with financial management or small enterprise development. JEL Classification: B10, B26, B30DOI: https://doi.org/10.26905/jkdp.v22i3.2096